2021
DOI: 10.3346/jkms.2021.36.e83
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Virologic Effectiveness of Remdesivir Treatment for Severe Coronavirus Disease 2019 (COVID-19) in Korea: a Nationwide Multicenter Retrospective Cohort Study

Abstract: Background Remdesivir is widely used for the treatment of coronavirus disease 2019 (COVID-19), but controversies regarding its efficacy still remain. Methods A retrospective cohort study was conducted to evaluate the effect of remdesivir on clinical and virologic outcomes of severe COVID-19 patients from June to July 2020. Primary clinical endpoints included clinical recovery, additional mechanical ventilator (MV) support, and duration of oxygen or MV support. Viral loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 28 publications
1
44
0
1
Order By: Relevance
“…12 Patients requiring mechanical ventilation prior to day 28 of hospitalization were less and the duration of mechanical ventilation was shorter in patients using RDV. 11 These findings supported the clinical efficacy of RDV treatment for COVID-19 patients.…”
Section: Remdesivir and Sars-cov-2 Viral Loadsupporting
confidence: 61%
See 1 more Smart Citation
“…12 Patients requiring mechanical ventilation prior to day 28 of hospitalization were less and the duration of mechanical ventilation was shorter in patients using RDV. 11 These findings supported the clinical efficacy of RDV treatment for COVID-19 patients.…”
Section: Remdesivir and Sars-cov-2 Viral Loadsupporting
confidence: 61%
“…From On the lower respiratory tract analysis, the RDV group also showed a higher increase in CT values (n = 33; median, 0.99; IQR, 0.26, 1.15) compared to the SoC group (n = 28; median, 0.75; IQR, -0.05, 0.99) but the difference was not significant (P = 0.291). 11 were no significant safety concerns with drug administration. 17 The study included 48 subjects taking RDV known to have comorbid diseases (cardiovascular disease, asthma, pulmonary disease, cancer, liver disease, kidney disease, diabetes and HIV).…”
Section: Resultsmentioning
confidence: 99%
“… 7 , 8 C t value has been also used to assess response to antiviral therapy. 9 However, several studies have shown that nasopharyngeal SARS‐CoV‐2 C t values are not associated with COVID‐19 severity and do not support a predictive role for the C t value in the clinical setting. 10 , 11 , 12 , 13 , 14 For example, in a report that included a total of 414 throat swabs collected from 94 patients, there was no obvious difference in viral loads across disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Entre os estudos de coorte encontrados, sete autores (Grein et al, 2020;Pasquini et al, 2020;Mendez-Echevaría et al, 2021;Flisiak et al, 2021;Ackley et al, 2021;Joo et al, 2021;Aiswarya et al, 2021) Como podemos observar, a maioria dos estudos encontrados relatou uma melhora no quadro dos pacientes tratados com Remdesivir, porém é importante ressaltar que a terapia com o medicamento também apresentou diversos efeitos colaterais, os quais podemos citar:…”
Section: Resultsunclassified